Analisis Produktivitas, Keuntungan, dan Efisiensi Biaya Usaha Budidaya Lebah Madu Trigona sp. di Kecamatan Landono Kabupaten Konawe Selatan - Pratiwi, Ni Putu Arin; Abdullah, Bahari; Dirgantoro, Muhammad Arief (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
This study aims to determine the productivity of Trigona sp beekeeping, know the benefits of Trigona sp beekeeping and find out the cost efficiency of Trigona sp beekeeping in Landono Subdistrict, Konawe Selatan Regency. This research was conducted in November 2019 to March 2020 using quantitative descriptive methods. Analysis of the data used in this research is productivity analysis, profit analysis, and cost efficiency analysis using the RC ratio. The results obtained, the average value of honey bee productivity in each bee colony produces 1.02 kg of honey, the average profit of Trigona sp beekeeping is Rp5,068,900, - and RC The average ratio of Trigona sp beekeeping is 3.01. RC ratio value> 1 which indicates that the Trigona sp honey beekeeping business is profitable and can be continued. Based on this research it is expected that the Trigona sp bee business can be better known and developed more broadly.